2016
DOI: 10.1007/s11936-016-0470-x
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Management of Abdominal Aortic Aneurysms: the Year in Review

Abstract: Endovascular aneurysm repair (EVAR) has become the predominant method of treatment for abdominal aortic aneurysms (AAA). The use of conscious sedation with local anesthesia and percutaneous femoral access has further decreased the morbidity of the procedure. Current devices can more effectively manage increasingly "hostile" aneurysm necks, while chimney grafts or dedicated fenestrated stent-grafts can be used for juxta-renal disease with favorable results. However, endovascular repair does present a new set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 84 publications
0
8
0
1
Order By: Relevance
“…Better preventive and bleeding avoidance strategies are needed if the full benefits of these new techniques are to be achieved. 5,[13][14][15]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Better preventive and bleeding avoidance strategies are needed if the full benefits of these new techniques are to be achieved. 5,[13][14][15]…”
Section: Discussionmentioning
confidence: 99%
“…Receiving 1 or more transfusions was associated with increased in-hospital mortality (adjusted odds ratio, 1.92; 95% CI, 1.63-2.21; P < .001), length of stay (adjusted multiplicative difference, 2.10; 95% CI, 11.96-2.25; P < .001), and health care cost (adjusted multiplicative difference, 1.72; 95% CI, 1.64-1.81; P < .001), compared with receiving no transfusion. The risk of dying (22.02% to 38.56% vs 8.21%), length of stay (median [IQR], 8 [2][3][4][5][6][7][8][9][10][11][12][13][14][15] to 13 [7][8][9][10][11][12][13][14][15]…”
Section: Impact Of Transfusionmentioning
confidence: 99%
“…Percutaneous access is associated with a lower frequency of groin infection or lymphocele, and a shorter procedure time and hospital length of stay compared with open surgery. The use of conscious sedation with local anesthesia and percutaneous femoral access has further decreased the morbidity of procedure [8]. Complications of endovascular repair include further aortic wall injury, access complications and contrast-induced nephropathy, but this treatment is associated with less perioperative morbidity and mortality [6].…”
Section: Discussionmentioning
confidence: 99%
“…This allows physicians to routinely test and optimise their strategies, to choose appropriate devices and identify potential problems in advance, both in basic and more complex cases. 47,48 A recent RCT showed that patient specific rehearsal using VR simulation effectively allows both experienced and less experienced endovascular teams to actively rehearse procedures and to adapt their treatment plans (e.g., C-arm angles for visualisation of landing zones, orientation of contralateral limb). It also enhances teamwork and reduces both minor (e.g., asking for the wrong endovascular tool) and major errors (e.g., inadvertently overstenting the internal iliac artery).…”
Section: Pre-operative Aims To Improve Practice and Outcomesmentioning
confidence: 99%